Performance Analysis of Employees of the Directorate General of Teachers and Educational Personnel Ministry of Education, Culture, Research and Technology - Martono, Dicky; Rivai Zainal, Veithzal; Hakim, Azis (Journal of Economics and Business UBS, 2023)
The aim of this research is to describe the performance of employees of the Directorate General of Teachers and Education Personnel of the Ministry of Education, Culture, Research and Technology. The research method used is descriptive qualitative research with observations and in-depth interviews. The results of the research are: Overall it is appropriate, but there is still work overlap that occurs. However, they have carried out their duties in accordance with their main duties and functions as well as their respective authorities in carrying out their work so that it is clear what is being done. There are supporting factors including leadership as a work partner. Provide encouragement and direction. Giving awards. Create a comfortable workplace. Be a role model for employees. Leadership must be truly accountable, because the leadership's responsibility is very important and determines the high and low levels of employee work results, as well as employee performance and morale. The inhibiting factors include a lack of increased discipline and a lack of management of organizational culture development. The strategy for improving employee performance at the Directorate General of Teachers and Education Personnel of the Ministry of Education, Culture, Research and Technology is by planning an organizational program, namely the process of planning, organizing, leading and controlling the efforts of organizational members as well as utilizing all organizational resources in order to achieve organizational goals. has been determined by the leadership.